Diversity and Abundance of Phytoplankton in the Coastal Waters of Batu Kijuk Sekotong, West Lombok - Nadiyah, Nurfadhilah; Idrus, Agil Al; Japa, Lalu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Sekotong is a region in the West Nusa Tenggara Province, characterized by its coastal area with significant potential natural resources for marine fisheries. The feasibility of water quality for marine aquaculture can be assessed through quantitative and qualitative tests on the biota inhabiting a water body, such as phytoplankton. This research aims to determine the abundance and diversity of phytoplankton in the coastal waters of Batu Kijuk. A 20 μm plankton net was used to filter seawater samples taken as much as 100 L of water. Preserving water samples using formalin with a concentration of 4%. Data analysis uses calculations of individual abundance, species diversity and dominance index. The random sampling method was used to determine the sampling location. The research results mean the average abundance of phytoplankton is 256,667 Ind/L. The species diversity index (H'=2.41) was grouped into an intermediate index and a species dominance index (C=0.13). The research results showed that the phytoplankton community identified in Batu Kijuk Beach waters consisted of 4 classes and 36 species.